Materials development and properties characterization of innovative magnetorheological (MR) fluids - Yang, Yong Bo (2010)
With the goal of developing innovative magnetorheological (MR) fluids, we performed the synthesis and characterization of new magnetic particles. With these particles, the properties of several new MR fluids were investigated. In the material synthesis, Fe304 nanoparticles have been obtained using vesicle method, the magnetite particles were encapsulated in the vesicles formed from cetyltrimethylammonium bromide (CTAB) and sodium octyl sulphate (SOS). These small particles have no sedimentation issue, but their magnetization saturation is around 60 emu/g, which is not high enough for MR fluids. To obtain particles with higher magnetization saturation, iron based Fe-M-B (M can be Co, Cr or Ni) particles were synthesized using borohydride reduction method. A maximum Ms of 153emu/g was achieved. And the particle size can be tailored from 40nm to 200nm by controlling the water/ethanol ratio ofthe solvent. The mechanical behavior of the synthesized nano-MR fluids was investigated through rheological testing under magnetic fields. It was found that the Fe-Cr-B based nanoMR fluids have the merits of both ferrofluids and conventional MR (C-MR) fluids. They have moderate yield stress, and they have good anti-sedimentation property. Based on the rheological characteristic of the nano-MR fluids, a convected Jeffrey model was used to predict their dynamic behaviors. The nano-MR fluids were obtained from a chemical method. While in a physical method, conventional MR fluids were mixed with ferrofluids. Experimentally it was found these ferrofluids based MR fluids (F-MR fluids) had comparable yield stress with C-MR fluids, while the anti-sedimentation properties were greatly improved. In addition to the magnetorheological study ofnano-MR fluids and F-MR fluids, two more topics have been particularly investigated.